Prediction of the transmission loss in a flexible chamber. (October 2018) - Torregrosa, A.J.; Gil, A.; García-Cuevas, L.M.; Quintero, P.; Denia, F.D.
Abstract: Acoustic components have been extensively studied supposing perfectly rigid behavior. Although some works have been performed for the radiated sound in the case of a flexible element, an important lack of information exists concerning transmission loss analysis. The current investigation proposes the study for a generic flexible expansion chamber. The analysis has been performed using two different methods: a resolution in the time domain, using a Finite Volume discretization for the fluid domain and a Finite Element discretization for the solid domain, and an approach in the frequency domain, using a Finite Element discretization for both fluid and solid. After studying the rigid case in order to tune up the simulation, the study of the flexible case shows a good agreement among both methods. The comparison of rigid and flexible expansion chambers shows the importance of accounting for these phenomena when the frequency content of the acoustic signal excites the natural modes of the structure.